Spoligotyping and drug sensitivity of Mycobacterium tuberculosis isolated from pulmonary tuberculosis patients in the Arsi Zone of southeastern Ethiopia. (January 2020) - Haile, B.; Tafess, K.; Zewude, A.; Yenew, B.; Siu, G.; Ameni, G.
Abstract: Tuberculosis (TB) is one of the leading causes of morbidity and mortality in different zones of Ethiopia. This study was undertaken to identify the strains of Mycobacterium tuberculosis and evaluate their drug sensitivity profiles in the Arsi Zone. A total of 111 isolates of M. tuberculosis from individuals with pulmonary TB were included and speciation and strain identification were performed using Region of difference 9 and spoligotyping, respectively. The drug sensitivity patterns were assessed using Bactec MGIT 960 SIRE and GenoType MTBDRplus line probe assays. Of 111 isolates, 83% were interpretable and 56 different spoligotype patterns were identified. From these, 22 patterns were shared types while the remaining 34 were orphans. The predominant shared types were spoligotype international type (SIT) 149 and SIT53, comprising 12 and 11 isolates, respectively. Euro-American lineage was the dominant lineage followed by East-African-Indian. Phenotypically, 17.2% of tested isolates were resistant to any first-line drugs and 3.1% were multidrug-resistant. Higher (6.2%) mono-resistance was observed to streptomycin, and no resistance was observed to rifampicin or ethambutol. Genotypically, five (5.4%) isolates were resistant to isoniazid and mutated at codon S315T1 of katG . In contrast, only 1.1% of the isolates were resistant to rifampicin and were mutated at codon S531L of rpoB gene. In this study, a high proportion of orphan strains were isolated, which could suggest the presence of new strains and a high percentage of mono-resistance, warranting the need to strengthen control efforts.